Combination of two chromophores: synthesis and PDT application of porphyrin-pentamethinium conjugate - Bříza, Tomáš; Králová, Jarmila; Cígler, Petr; Kejík, Zdeněk; Poučková, Pavla; Vašek, Petr; Moserová, Irena; Martásek, Pavel; Král, Vladimír (Bioorganic & medicinal chemistry letters, 2012)
A general method for the synthesis of a novel porphyrin with pentamethine periphery substitution is described. The combination of two chromophoric systems, a porphyrin macrocycle and a polymethine moiety was achieved by transformation of tetrapyridyl porphyrin. The synthetic strategy included conversion of the tetrapyridyl porphyrin to its corresponding 2,4-dinitrophenylpyridinuim salt, which was subsequently converted to tetrakis(meso-pentamethinium salt) on the porphyrin core. This novel porphyrin exhibited PDT properties as manifested by the induction of apoptosis in the myeloid cell line HL-60 and the effective reduction of amelanotic melanoma in nude mice.
Keywords: buněčná smrt; Bis-Trimethylammonium Compounds; HL-60 Cells; soli; apoptóza; porfyriny; Porphyrins; bistrimethylamoniové sloučeniny; Melanoma; Time Factors; fragmentace DNA; DNA Fragmentation; fotochemoterapie; Mice; Cell Death; Neoplasms; chemické modely; Mice, Nude; melanom; zvířata; Humans; racionální návrh léčiv; Salts; nádory; Photochemotherapy; myši nahé; inhibiční koncentrace 50; časové faktory; myši; Models, Chemical; Inhibitory Concentration 50; HL-60 buňky; Drug Design; lidé; Apoptosis; Animals